Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Pegawai dimediasi oleh Komitmen Organisasi - Ahmad Fauzan; Zulaspan Tupti; Fajar Pasaribu; Hasrudy Tanjung (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to determine the Effect of Transformational Leadership and Organizational Culture on Employee Performance Mediated by Organizational Commitment at the Regional Representatives Council Office of North Sumatra Province. This type of research is survey research because it takes samples from one population. This study uses an explanatory research approach, which aims to explain the causal relationship between the research variables and the testing hypothesis. This research is included in the category of causal research using a quantitative approach. The population in this study were all employees in the Regional People's Legislative Council Office of North Sumatra Province, consisting of 110 employees. As for determining the number/size of the sample in this study using a saturated sample, all members of the population were used as a sample of 110 employees of the Regional Representatives Council of North Sumatra Province. Data collection techniques used are interviews/interviews and questionnaires/questionnaires. This data will be analyzed using a quantitative approach using statistical analysis, namely the partial least squares – structural inquiry model (PLS-SEM) which aims to carry out path analysis (path) with latent variables. Data analysis techniques in this study used a quantitative approach using statistical analysis using the Outer Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study indicate that (1) Transformational leadership directly has a significant effect on employee performance at the Regional People's Representative Council Office of North Sumatra Province. (2) Directly organizational culture has a significant effect on employee performance at the Regional People's Representative Council Office of North Sumatra Province. (3) Directly organizational commitment has a significant effect on employee performance at the Regional People's Representative Council Office of North Sumatra Province. (4) Transformational leadership directly has a significant effect on organizational commitment at the Regional People's Representative Council Office of North Sumatra Province. (5) Directly organizational culture has a significant effect on organizational commitment at the Regional People's Representative Council Office of North Sumatra Province. (6) Indirectly organizational commitment can mediate the effect of transformational leadership on employee performance at the Regional People's Representative Council Office of North Sumatra Province. (7) Indirectly organizational commitment can mediate the influence of organizational culture on employee performance at the Regional People's Representative Council Office of North Sumatra Province.